Fertility Rates Following Fixed-Time Artificial Insemination in Dairy Heifers in a Practical Progesterone-Based Protocol - Oliveira, Leticia Zoccolaro [UNESP]; Martins Hossepian de Lima, Vera Fernanda [UNESP]; Oliveira, Clara Slade [UNESP]; Alves, Benner Geraldo; Graff, Hugo Borges; dos Santos, Ricarda Maria (Universidade Federal do Rio Grande do Sul (UFRGS), 2011)
Background: In bovines, more efficient management practices are important for maximizing profitability. In order to increase the pregnancy rates in artificial insemination (AI) programs, several hormonal protocols were developed to synchronize the follicular wave and the moment of ovulation in beef and dairy cattle. In dairy cattle, detection of estrus can be difficult due to a number of factors including the incidence of silent estrus. Hormonal treatments designed to control both luteal and follicular function has permitting efficient synchronizations of time of ovulation. Thus, the AI can be performed in a large number of animals on a fixed schedule without the need for detection of estrus. Using these management techniques, the fixed-time artificial insemination (TAI) can overcome the problem of accurate estrus detection and help in reducing the incidence of repeat breeding. In addition, with TAI in cattle operations, it is possible to facilitate management practices and commercialization, and to reduce the time and semen wasting with animals inseminated at incorrect times. The investigation of practical and efficient TAI protocols is important for reducing the labor and animal handling of TAI in dairy cattle, as well as for increasing the profitability of the cattle management system. This study was carried out in order to investigate the effectiveness of TAI in dairy heifers treated with a practical progesterone-based protocol.Materials, Methods & Results: This experiment was conducted at the university farm located in southwestern Brazil, during May 2009. Thirty-nine cycling crossbred dairy heifers were employed in this study. All animals received a single intramuscular injection of estradiol benzoate and intravaginal progesterone releasing device in a random stage of the estrous cycle (Day 0). on day 7 the animals were treated with PGF2a analogue and on day 9 the device was removed. Forty-eight hours after the device removal (day 11) a synthetic analogue of GnRH was administered and the animals were fixed-time artificially inseminated at the time of GnRH injection. The inseminations were performed using four different batches from the same Holstein bull. Among the heifers that were synchronized (87.2%), 30.8% ovulated until 24 h after TAI and 56.4% ovulated between 24 and 32 h after TAI. The conception rate was 61.5%. No effects of ovulation time in conception rates were detected. The conception rate from heifers that ovulated until 24 h after TAI was 58.3% and from heifers that ovulated between 24 and 32 h after TAI was 77.3%. The mean of ovulatory follicle in heifers that ovulated until 24 h was 14.3 mm and in heifers that ovulated between 24 and 32 h was 11.9 mm.Discussion: Taking together, the findings of the present study, along with those of others, emphasize the concept that development of practical methods for TAI offers significant advantages to dairy producers if conception rates are close or greater to those obtained after breeding at detected estrus. Thus, the results of the present study reinforce the possibility of making dairy cattle production more cost-effective using TAI. In conclusion, with the progesterone-based TAI protocol of the present experiment all synchronized animals ovulated up to 32 h after GnRH+TAI and no effects of ovulation time related to conception rate was detected. The exogenous control of luteal and follicular development facilitated the reproductive management and animal handling. Also, inseminating the heifers at the moment of GnRH injection in a progesterone-based TAI protocol is a practical strategy and provided satisfactory results regarding ovulation and conception rates in dairy heifers.
Keywords: Conception rate; Heifers; ovulation; Progesterone